READING MOTIVATION OF TENTH GRADE STUDENTS AT SMA ADVENT UNKLAB AIRMADIDI - Manuas, Maissy Jearmita; Tatipang, Devilito P.; Pratasik, Geral (English Education Department, 2022)
As we all know in the world of education reading is an important thing Because by reading we can find various important things and also add knowledge Of course in reading we need motivation to be able to read long This study aims to measure and find out how much motivation 10th graders have to read By using quantitative methods this study succeeded in finding out how much interest in reading the 10th graders had based on gender In this study also given some understanding of what motivation is And the results of this study showed that the teacher should provide interesting reading or writing so that it creates enthusiasm in reading to students The perceptions of male and female students in this school were found to be the same so there was no difference between who was more motivated in reading in addition this the result of this study is expected to help readers and future researchers in discussing similar problems< p>